Effects of land use change and seasonal variation in the hydrophysical properties in Vertisols in northeastern Mexico. (1st May 2019) - Yáñez‐Díaz, María I.; Cantú‐Silva, Israel; González‐Rodríguez, Humberto; Sánchez‐Castillo, Laura
Abstract: The impact of the use of natural resources associated with anthropogenic activities has increased evidently, mainly through land use changes which have altered hydrophysical properties of soils. We hypothesized that, in the same soil type (Vertisol), four types of land use system (grassland, agricultural, Eucalyptus plantation and thornscrub) and seasonal variation can modify the soil hydrophysical properties. Results showed significant differences between land use systems and seasons for hydraulic conductivity ( K ), infiltration capacity ( fp ) and cumulative infiltration ( fc ). There were no seasonal differences in soil penetration resistance ( SPR ), bulk density ( ρd ) and total porosity ( φP ). Grassland presented higher values for ρd (1.2 g cm −3 ) and SPR (5.3 kg cm −2 ) and lower for K (0.8 × 10 −5 cm s −1 ) and φP (53%), unlike thornscrub. Agriculture presented lower SPR (0.4 kg cm −2 ), while plantation showed similar values when compared to the thornscrub. Kostiakov infiltration model was fitted to land use infiltration curves, showing differences between land use and season. The values for fp oscillated between 53.6 and 548.8 mm hr −1 and fc ranged from 105.3 to 1, 061 mm. The order of the infiltration values goes as follows: agriculture > plantation > thornscrub > grassland. Land use changes in Vertisols induced modification of soil physical properties affecting processes like permeability, soil compaction and water availability.